A Semiotic Analysis of Signs Found in USTP PT. Graha Cakra Mulia - Kirani Sitohang, Ivana Nadya; Hidayat, Rekha Ramadhani; Rivaldo (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research examines the form of signs found in PT. Graha Cakra Mulia and the meaning or idea that the sign represents. This research uses descriptive qualitative approach such the writers analyze the visual signifier and concept of meanings as signified the data with analyzed based on Saussure model of sign which consist of signifier and signified. The writers use 30 data taken from PT. Graha Cakra Mulia. The result of this research is the writers find there are some visual image and text in each sign that represented the signifier and signified.